(untitled) (Scientific journal of the Fergana State University, 2026)
This article highlights the challenging early life of Academician Buriboy Akhmedov (1924–2002), who played a significant role in the development of historiography and source studies in Uzbekistan. Research indicates that his childhood coincided with the Soviet government’s implementation of the “New Economic Policy” (1921–1928) and the “Land and Water Reform” (1921–1929) in the countries of Central Asia. His adolescence took place during the Second World War (1939–1945), where he served directly at the front, while his youth passed under the difficult economic conditions of the post-war period. The article examines these aspects based on documents preserved in the scholar’s personal archive.